2021
DOI: 10.3390/f12030362
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid Loop-Mediated Isothermal Amplification Assay for the Detection of Dothistroma septosporum

Abstract: A Loop-Mediated Isothermal Amplification (LAMP) assay was developed for the detection of the pine pathogen Dothistroma septosporum (G. Dorog.) M. Morelet. The specificity of the LAMP assay was tested using a selection of pine needle fungi, including Dothistroma pini Hulbary, and Lecanosticta acicola (Thüm.) Syd.; only D. septosporum DNA was amplified by the test. In terms of sensitivity, the assay was able to detect as little as 1 pg of total D. septosporum DNA. This assay enables DNA extracted from diseased h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…These assays also have the potential to be deployable in-field, directly at point-of-care with the use of portable devices developed for supporting LAMP reactions (e.g., Genie ® II and III by OptiGene Limited, Horsham, UK) [55,56,59]. To the best of our knowledge, there are no published LAMP-based assays targeting L. acicola and D. pini, while for D. septosporum a LAMP-based assay has been recently published [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These assays also have the potential to be deployable in-field, directly at point-of-care with the use of portable devices developed for supporting LAMP reactions (e.g., Genie ® II and III by OptiGene Limited, Horsham, UK) [55,56,59]. To the best of our knowledge, there are no published LAMP-based assays targeting L. acicola and D. pini, while for D. septosporum a LAMP-based assay has been recently published [60].…”
Section: Discussionmentioning
confidence: 99%
“…All these features make it an ideal solution for in-field point-of-care molecular diagnostics [55]. In addition, the technology has already proved successful for the detection of pathogens in forest systems [54,[56][57][58][59][60]. The aim of this study was to develop three LAMP-based diagnostic assays for the rapid and early detection of the pine pathogens L. acicola, D. pini and D. septosporum.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of D. septosporum infected pines that we have identified in Alberta were lodgepole pine (Feau et al, 2021); however, natural infection of seedlings of the two major species of Pinus in Alberta and their hybrid included in this trial clearly showed that jack pine and the hybrid are also susceptible to D. septosporum infection. This confirms earlier reports in the literature (Funk & Parker, 1966;Jankovský et al, 2004).…”
Section: Re Sults and Discussionmentioning
confidence: 69%
“…The lack of records of D. septosporum on jack pine and the hybrid from the Canadian Forest Insect and Disease Survey, and other publications such as the Canadian Plant Disease Survey, suggest that the incidence of the pathogen on jack pine and the hybrid have historically been low. The emergence of the pathogen in Alberta (Feau et al, 2021) and the observations within this trial, suggest that further monitoring of infection of Pinus spp. by D. septosporum should be conducted to evaluate the risk of D. septosporum and Dothistroma needle blight in the boreal forest.…”
Section: Re Sults and Discussionmentioning
confidence: 72%
See 1 more Smart Citation